Pilot testing of a heat integrated 0.7 MWe CO2 capture system with two-stage air-stripping: Amine degradation and metal accumulation. (September 2017) - Thompson, Jesse G.; Bhatnagar, Saloni; Combs, Megan; Abad, Keemia; Onneweer, Femke; Pelgen, Jonathan; Link, David; Figueroa, Jose; Nikolic, Heather; Liu, Kunlei
Graphical abstract: Highlights: A 0.7 MWe pilot post-combustion CO2 capture unit with air stripping was tested. Material corrosion was a source of high Fe and Cu levels in the solvent. Degradation levels were comparable to previously published reports with 30% MEA. The impact of the secondary air stripper on solvent oxidation was negligible. Abstract: An advanced 0.7 MWe small pilot coal-fired post-combustion CO2 capture system with heat integration combined with two-stage stripping was tested on a slipstream of flue gas by the University of Kentucky Center for Applied Energy Research (UKy-CAER). Evaluation of solvent degradation products was performed to determine the impact of oxygen exposure due to incorporation of the secondary air stripper into the conventional amine absorber/stripper system. The overall degradation rates and products observed during the testing campaign were comparable to previously published reports using 30% monoethanolamine (MEA) as the baseline/commissioning solvent. The rates of heat stable salt accumulation and amine degradation were similar to those from conventional CO2 capture systems using MEA. Metal accumulation as the result of material corrosion inside the system from an improperly constructed material was observed. The impact of the secondary air stripper appears negligible relative to other published MEA campaigns tested at similar flue gas conditions and system operating hours.